'You are the victim now': Factoría de Terror and immersive horror theatre in contemporary Spain. Issue 2 (1st October 2019) - Carrera Garrido, Miguel
This article focuses on Spanish contemporary horror theatre, in particular on a group called Factoría de Terror (Factory of Horror). Normally disregarded by horror scholars – not only in the Spanish academia – theatre has given birth to some of the most shocking expressions in the history of the genre. Here we focus our attention on shows that involve immersion and participation of the spectators, for these are strategies that can only be implemented on the stage, and result in powerful effects when applied to the aesthetics and ethos of horror. Factoría de Terror's projects will serve to illustrate this insufficiently acknowledged potential of theatrical representation.